Real Time Delta Extraction Based on Triggers to Support Data Warehousing - Valencio, Carlos Roberto [UNESP]; Marioto, Matheus Henrique [UNESP]; Donega Zafalon, Geraldo Francisco [UNESP]; Machado, Jose Marcio [UNESP]; Momente, Julio Cesar [UNESP]; Horng, S. J. (Ieee, 2013)
Nowadays large corporations require integrated data from diverse sources, leading to the use of data warehouse architectures for this purpose. To bypass problems related to the use of computational resources to process large volumes of data, an ETL (Extract, Transform and Load) technique with zero latency can be used, that works by constantly processing small data loads. Among the extraction techniques of the zero latency ETL are the use of logs, triggers, materialized views and timestamps. This paper proposes a structure capable of performing this task by means of triggers and a tool developed for the automatic generation of the SQL (Structured Query Language) code to create these trigger, besides showing its performance and comparing it to other techniques. Said method is relevant for the extraction of portions of selected information as it permits to combine conventional and real time ETL techniques.
Keywords: data warehouse; ETL (Extract Transform and Load); CDC (Change Data Capture); trigger; automatic code generation